Christian Education Through Mapalus Culture in North Minahasa District - Tumundo, Deyvi; Undap, Andy P.P.; Poluan, Agnes Relly (Peneliti.net, 2024)
Mapalus culture is a practical form of the Sitou Timou Tumou Tou philosophy, which is an activity of community life with the nature of mutual cooperation (cooperation) which is inherent in every human being, son and daughter of the Minahasa ethnic community. Mapalus literally means mutual cooperation or cooperation. Its application in people's lives includes almost all work, whether in mourning (misfortune), Mapalus culture contains very strong Christian values ​​such as family, love and peace. The impact of modernization with various technological advances is starting to displace shared values. From this background, the researcher felt interested in researching